Imaging of Formaldehyde in Live Cells and Daphnia magna via Aza-Cope Reaction Utilizing Fluorescence Probe With Large Stokes Shifts - Yang, Mingwang; Fan, Jiangli; Du, Jianjun; Long, Saran; Wang, Jia; Peng, Xiaojun (Frontiers in Chemistry, 2018)
Formaldehyde (FA), a highly reactive carbonyl species, plays significant role in physiological and pathological functions. However, elevated FA will lead to cognitive impairments, memory loss and various neurodegenerative diseases due to its potent DNA and protein cross-linking mechanisms. In this work, a fluorescence probe, BD-CHO, based on benz-2-oxa-1, 3- diazole (BD) skeleton, was designed and synthesized for detection of FA via Aza-Cope reaction with high selectivity and large Stokes shifts (about 118 nm). BD-CHO was successfully applied to monitor the changes FA level in living cells, and kidney tissues of mice. Importantly it was the first time that BD-CHO was used for visualizing exogenous FA changes in Daphnia magna through fluorescence microscopy, demonstrating its potential application for studies of biological processes associated with FA.